Legionellosis Outbreak Associated With a Hotel Fountain. (28th December 2015) - Smith, Shamika S.; Ritger, Kathy; Samala, Usha; Black, Stephanie R.; Okodua, Margaret; Miller, Loretta; Kozak-Muiznieks, Natalia A.; Hicks, Lauri A.; Steinheimer, Craig; Ewaidah, Saadeh; Presser, Lance; Siston, Alicia M.
Abstract: Background. In August 2012, the Chicago Department of Public Health (CDPH) was notified of acute respiratory illness, including 1 fatality, among a group of meeting attendees who stayed at a Chicago hotel during July 30–August 3, 2012. Suspecting Legionnaires' disease (LD), CDPH advised the hotel to close their swimming pool, spa, and decorative lobby fountain and began an investigation. Methods. Case finding included notification of individuals potentially exposed during July 16–August 15, 2012. Individuals were interviewed using a standardized questionnaire. An environmental assessment was performed. Results. One hundred fourteen cases were identified: 11 confirmed LD, 29 suspect LD, and 74 Pontiac fever cases. Illness onsets occurred July 21–August 22, 2012. Median age was 48 years (range, 22–82 years), 64% were male, 59% sought medical care (15 hospitalizations), and 3 died. Relative risks for hotel exposures revealed that persons who spent time near the decorative fountain or bar, both located in the lobby were respectively 2.13 (95%, 1.64–2.77) and 1.25 (95% CI, 1.09–1.44) times more likely to become ill than those who did not. Legionella pneumophila serogroup 1 was isolated from samples collected from the fountain, spa, and women's locker room fixtures. Legionella pneumophila serogroup 1 environmental isolates and a clinical isolate had matching sequence-based types. Hotel maintenance records lacked a record of regular cleaning and disinfection of the fountain. Conclusions. Environmental testing identified Legionella in the hotel's potable water system. Epidemiologic and laboratory data indicated the decorative fountain as the source. Poor fountain maintenance likely created favorable conditions for Legionella overgrowth.